UJI KADAR TIMBAL (Pb) IKAN LAIS (Kryptopterus apogon) DI PERAIRAN SUNGAI MUSI PALEMBANG DENGAN METODE SPEKTOFOTOMETRI SERAPAN ATOM (SSA) - Monica, Tiara; Marpaung, Mauritz Pandapotan (Al-Ard: Jurnal Teknik Lingkungan, 2026)
Musi river is the longest river on the island of Sumatra which has the potential to be polluted due to heavy metal content that can threaten the life of biota such as fish. The study aimed to analyze lead (Pb) contamination in Lais fish and river water in the Musi River Palembang. A total of three samples of Lais fish and Musi river water obtained from the areas of Jakabaring, Sungki, and Silaberanti were subjected to wet digestion using HNO3 and H2O2. The destruction results were analyzed for Pb metal content through Atomic Absorption Spectrophotometer (AAS) with standard a solution of Pb(NO3)2 at 217,0 nm. The results showed that all of Lais fish and Musi river water did not contain lead (Pb) metal contamination.